Tests to determine LC50 and discriminating doses for macrocyclic lactones against the cattle tick, Boophilus microplus - Sabatini, G. A.; Kemp, D. H.; Hughes, S.; Nari, A.; Hansen, J. (Elsevier B.V., 2001)
Laboratory tests were carried out on larvae and adults of the cattle tick Boophilus microplus to determine the toxicity of macrocyclic lactone acaricides (MLs). Technical and commercial MLs were used in larval packet test (LPT), larval immersion test (LIT) and adult immersion test (AIT). Tn LIT and AIT the toxicity of MLs was much higher than for LPT. In the AIT, diluting the injectable formulation of MLs in water was as effective as dilution in ethanol + Triton X-100. LC50, LC99.9 and 95% confidence limits were determined so that a discriminating dose (DD) could be set for larval and adult tests in order to diagnose potential resistance to MLs in field samples of the tick. These DDs are for Australian strains of B. microplus and may not be suitable for other strains until further work is carried out.The value of these diagnostic tests can only be verified if or when resistance to MLs emerges in ticks. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Boophilus microplus; macrocyclic lactones; resistance tests